Nonclassical Biological Activities of Quinolone Derivatives - Mohsen Daneshtalab; Abeer Ahmed (Frontiers Media S.A., 2011)
Quinolones are considered as a big family of multi-faceted drugs; their chemical synthesis is flexible and can be easily adapted to prepare new congeners with rationally devised structures. This is shown by the description of many thousands of derivatives in the literature. Scientists could accurately describe their QSAR, which is essential for effective drug design. This also gave them the chance to discover new and unprecedented activities, which makes quinolones an endless source of hope and enables further development of new clinically useful drugs. Quinolones are among the most common frameworks present in the bioactive molecules that have dominated the market for more than four decades. Since 1962, 4(1H)-quinolone-3-carboxylic acid derivatives are widely used as antibacterial agents. Quinolones have a broad and potent spectrum of activity and are also used as second-line drugs to treat tuberculosis (TB). Recently, quinolones have been reported to display "nonclassical" biological activities, such as antitumor, anti-HIV-1 integrase, anti- HCV-NS3 helicase and -NS5B-polymerase activities. The present review focuses on the structural modifications responsible for the transformation of an antibacterial into an anticancer agent and/or an antiviral agent. Indeed, quinolones' antimicrobial action is distinguishable among antibacterial agents, because they target different type II topoisomerase enzymes. Many derivatives of this family show high activity against bacterial topoisomerases and eukaryotic topoisomerases, and are also toxic to cultured mammalian cells and in vivo tumor models. Moreover, quinolones have shown antiviral activity against HIV and HCV viruses. In this context the quinolones family of drugs seem to link three different biological activities (antibacterial, anticancer, and the antiviral profiles) and the review will also provide an insight into the different mechanisms responsible for these activities among different species. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.